Analisis Peran Kepala Desa Dalam Pemberdayaan Masyarakat Desa Sriwedari Kecamatan Jaken Kabupaten Pati - Puput Nur Agustin; Evi Priyanti (Peneliti.net, 2022)
Empowerment of rural communities is one of the efforts to improve community welfare, through several activities including increasing community initiatives and self-help, environmental and housing improvement, development of village economic enterprises, development of village financial institutions, as well as activities that can increase the community's ability to increase income. production. Therefore, in building village communities, especially in the socio-economic field, a leader is needed, in this case the Village Head who is expected to function as a source of innovation, coach, direct and function as a communicator to convey ideas or ideas. to the village community, in order to increase the initiative and creativity of the community in processing, maintaining and utilizing the surrounding resources, to achieve a better standard of living. As a leader, the village head is given the task of prospering the community in his village, the empowerment process can be carried out in various ways and the source of funding has been regulated by law. This study aims to determine the role of the Sriwedari Village Head in community empowerment. This study uses a qualitative approach. From the results of the research that has been carried out, it can be concluded that the role of the Sriwedari Village Head in community empowerment is good, it can be seen from several empowerment programs in the village, namely physical empowerment such as infrastructure development. : construction of drainage, construction of rice fields, and repair of bridges, while non-physical empowerment includes counseling or socialization in the context of increasing community knowledge and skills.